Immobilization of soil exogenous lead using raw and activated phosphate rocks. Issue 1 (5th February 2013) - Jiang, Guanjie; Liu, Yonghong; Fu, Qingling; Huang, Li; Zhang, Junqing; Hu, Hongqing
<x xml:space="preserve">Abstract</x> Phosphate rock (PR) has been widely and successfully used in immobilization of lead in contaminated soils. However, application of oxalic acid‐activated PR (APR) in the immobilization of lead and particularly investigations about the lead form in the contaminated soils are limited. Exogenous lead (Pb) immobilization was studied by Tessier's sequential extraction procedures after applying raw PRs and oxalic acid APRs into the yellow cinnamon soil (S1) and latosol soil (S2) at four levels of 0 (CK), 50, 500, and 2000 mg P kg−1 soil. The PRs selected were Nanzhang PR (NPR) and Kaiyang PR (KPR), and their activation products were ANPR and AKPR. The results indicated that the content of exchangeable Pb in two soils decreased gradually with the rising PRs amount compared with the control, within 0–7.5 mg kg−1 in S1 and 0–64.1 mg kg−1 in S2. The content of carbonate‐bound Pb changed marginally in S1 while increased substantially in S2 with the increase of PR amount; the change of Fe–Mn oxide‐bound Pb content showed similar change as the carbonate‐bound Pb and organic compound‐bound Pb increased generally. The residue fraction of Pb changed a little for all treatments. To sum up, after applying the testing PRs in two soils, the content of exogenous exchangeable Pb decreased in all treatments and residual fraction augmented conversely in most treatments. Therefore, Pb had been immobilized effectively by PR in thetwo soils and a better fixation effect obtained in APR. ©2013 American Institute of Chemical Engineers Environ Prog, 33: 81–86, 2014